2018
DOI: 10.1186/s12957-018-1327-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of skeletal muscle mass during neoadjuvant treatments correlates with worse prognosis in esophageal cancer: a retrospective cohort study

Abstract: BackgroundNutritional deficits, cachexia, and sarcopenia are extremely common in esophageal cancer. The aim of this article was to assess the effect of loss of skeletal muscle mass during neoadjuvant treatment on the prognosis of esophageal cancer patients.MethodsEsophageal cancer patients (N = 115) undergoing neoadjuvant therapy and surgery between 2010 and 2014 were identified from our surgery database and retrospectively analyzed. Computed tomography imaging of the total cross-sectional muscle tissue measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 30 publications
7
59
0
1
Order By: Relevance
“…During the course of neoadjuvant therapy we observed a statistically significant loss of muscle mass and consequently increased percentage of sarcopenic patients in the whole study population. These findings have also been described in previous retrospective studies and have been associated with inferior survival [23, 24].…”
Section: Discussionsupporting
confidence: 87%
“…During the course of neoadjuvant therapy we observed a statistically significant loss of muscle mass and consequently increased percentage of sarcopenic patients in the whole study population. These findings have also been described in previous retrospective studies and have been associated with inferior survival [23, 24].…”
Section: Discussionsupporting
confidence: 87%
“…Kamitani et al also found that ∆SMI (%) <−12.5% was a significant prognostic factor for OS, and pre-and post-NAT sarcopenia were not associated with OS [29]. Similar to these results, Järvinen et al reported that a ∆SMI (%) <−2.98% during NAT was related to poor OS in the multivariable analysis, whereas post-NAT sarcopenia did not significantly affect OS and complication rates [30]. RFS was also analyzed in this study, but ∆SMI (%) <−2.98%, pre-and post-NAT sarcopenia all did not affect RFS.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, only a few studies included patients who received NACRT instead of chemotherapy as a NAT, and none of these studies demonstrated a significant relationship between sarcopenia and OS [17,23]. Meanwhile, studies on the relationship between the amount of skeletal muscle loss and survival outcomes of esophageal cancer showed relatively consistent results for OS, although they still showed contradictory results for RFS [28][29][30][31][32]. Reisinger et al showed that the amount of muscle mass loss during NACRT was associated with postoperative mortality in patients with stage III-IV tumors [28].…”
Section: Discussionmentioning
confidence: 99%
“…28 Prevalence of sarcopenia in studies on correlation between muscle area and survival in esophageal cancer can range widely from 16%-80%. [29][30][31] Choosing the right cutoff values for defining sarcopenia and myosteatosis can be challenging. In keeping with the definition of sarcopenia as absolute muscle mass below the 5th percentile of the population 32 proposed using the 5th percentile for cutoff values for SMI and MA in non-elderly (age 20-60) to avoid age related muscle loss.…”
Section: Discussionmentioning
confidence: 99%